Characterization of a fatty acid binding protein from the swimming crab Portunus trituberculatus and its effects on the composition of fatty acids in different tissues. Issue 1 (2nd January 2018) - Tang, Yujie; Li, Ye; Zhang, Dijun; Su, Xiurong; Zhang, Diya
Abstract: Fatty acid binding proteins (FABPs) belonging to the lipocalin protein family, have an affinity for fatty acids (FAs) and participate in both the transport of FAs and lipid metabolism. In this study, a 909-bp full-length pt-FABP cDNA containing a 411-bp open reading frame (ORF) was obtained from the swimming crab Portunus trituberculatus . Quantitative real-time PCR revealed that during larval development, pt-FABP expression increased gradually from the zoea to the megalopa, and decreased in the juvenile crab. pt-FABP mRNA was detected at the highest level in the testis, followed by the muscles, with the lowest level in the hepatopancreas. The composition of fatty acids in three different tissues from crabs of different sex was detected by gas chromatography–mass spectrometry (GC-MS). The results indicated that the FA profile was in accordance with the expression of pt-FABP, which suggested that pt-FABP participates in the unsaturated fatty acid transportation and storage system of P. trituberculatus .